MANFAAT INDUSTRIAL VISIT DALAM MENINGKATKAN PENGETAHUAN MAHASISWA PADA PROSES PEMBUATAN TEH BUTONG - Austin Alexander Parhusip; Aulia Ramadhani (JURNAL PENGABDIAN MANDIRI, 2025)
Industrial visits are an effective educational method for increasing student knowledge, especially in the context of the Butong Tea making process at PT Perkebunan Nusantara IV. This activity provides an opportunity for students to see firsthand the production process and understand the various technical and managerial aspects involved. Through this visit, students can connect the theory learned in class with real practice in the field, thereby deepening their understanding of the food industry. This industrial visit was carried out in Sidamanik District, Simalungun Regency, North Sumatra. The methods used were interviews and observation. Data collection was carried out by means of interviews, and the data taken was qualitative which was then analyzed descriptively